Statutory provisions of Malaysian law to subdue deviant teachings in the religion of islam and its implication / Zanirah Mustafa@Busu ...[et al.]. - Mustafa @ Busu, Zanirah; Mohd Firdaus Kozako, Intan Nurul 'Ain; Mohamed, Abdul Majid Tahir; Junoh, Noraini; Jusoh, Nor Asmira; Mat Zin, Mohd Nazri (2021)
Deviant teachings that are contrary to the recognised religions often disturb the peace and harmony of society. The aspect of aqidah (faith) is the core of religion for a Muslim. This paper explained the applicable statutory provisions of law in dealing with cases of deviant teachings in Malaysia. This paper attempted to relate instances of deviant teachings and the penalties prescribed by the Shariah Law as well as other general law. The paper also tried to provide exposure to the clauses contained in the existing legal provisions and significant forms of punishment. The methodology adopted in this paper was doctrinal in nature whereby methods of library research were resorted to in collecting data related to the statutory provisions governing deviant teachings and criminal offences relating to aqidah. Statistics showed that the number of cases for deviant teaching is increasing each year. The findings from this research showed that the current punishment and penalty are not sufficient to curb the offence committed and to create awareness among the public. This paper suggested that the relevant authorities should increase the severity of the punishment and widen the jurisdiction to control cases of deviant teaching in Malaysia. Members of the Muslim community should be given more exposure on its importance.